Whole body-electromyostimulation effects on serum biomarkers, physical performances and fatigue in Parkinson’s patients: A randomized controlled trial - di Cagno, Alessandra; Buonsenso, Andrea; Centorbi, Marco; Manni, Luigi; Di Costanzo, Alfonso; Casazza, Giusy; Parisi, Attilio; Guerra, Germano; Calcagno, Giuseppe; Iuliano, Enzo; Soligo, Marzia; Fiorilli, Giovanni; et al. (Frontiers in Aging Neuroscience, 2023)
Background Whole-body electromyostimulation (WB-EMS) was never previously applied to Parkinson’s disease (PD) patients. This randomized controlled study aimed to find the most effective and safe WB-EMS training protocol for this population. Methods Twenty-four subjects (age: 72.13 ± 6.20 years), were randomly assigned to three groups: a high-frequency WB-EMS strength training group (HFG) (rectangular stimulation at 85 Hz, 350 μs, 4 s stimulation/4 s rest), a low-frequency WB-EMS aerobic training group (LFG) (rectangular stimulation 7 Hz, 350 μs, with a continuous pulse duration), and an inactive control group (CG). Participants of the two experimental groups underwent 24 controlled WB-EMS training sessions, with a duration of 20 min each, during 12-week intervention. Serum growth factors (BDNF, FGF-21, NGF and proNGF), α-synuclein, physical performance and Parkinson’s Disease Fatigue Scale (PFS-16) responses were analyzed to evaluate the pre-post variation and differences among groups. Results Significant interactions of Time*Groups were detected for BDNF (Time*Groups p = 0.024; Time*CG, b = −628, IC95% = −1,082/−174, p = 0.008), FGF-21 (Time*Groups p = 0.009; Time*LFG b = 1,346, IC95% = 423/2268, p = 0.005), and α-synuclein (Time*Groups p = 0.019; Time*LFG b = −1,572, IC95% = −2,952/−192, p = 0.026). Post hoc analyses and comparisons of ΔS (post–pre), performed independently for each group, showed that LFG increased serum BDNF levels (+ 203 pg/ml) and decreased α-synuclein levels (−1,703 pg/ml), while HFG showed the opposite effects (BDNF: −500 pg/ml; α-synuclein: + 1,413 pg/ml). CG showed a significant BDNF reduction over time. Both LFG and HFG showed significant improvements in several physical performance outcomes and the LFG showed better results than HFG. Concerning PFS-16, significant differences over time (b = −0.4, IC95% = −0.8/−0.0, p = 0.046) and among groups (among all groups p < 0.001) were found, and the LFG exhibited better results than the HFG (b = −1.0, IC95% = −1.3/−0.7, p < 0.001), and CG (b = −1.7, IC95% = −2.0/−1.4, p < 0.001) with this last one that worsened over time. Conclusion LFG training was the best choice for improving or maintaining physical performance, fatigue perception and variation in serum biomarkers. Clinical trial registration https://www.clinicaltrials.gov/ct2/show/NCT04878679, identifier NCT04878679.